POPULASI ORONG-ORONG (GRYLLOTALPA SPP.) DAN KERUSAKAN TANAMAN PADI MUSIM TANAM GADU DI PUNGGUR, LAMPUNG TENGAH - Solikhin Solikhin; Purnomo Purnomo (Jurnal Agrotek Tropika, 2020)
Rice are the crop favored by many pest from beginning of growth until harvest. Mole cricket  is a pest commonly found in the early vegetative phase. This study aims to determine population of mole cricket and the level of attack on rice  in 2014 Gadu planting season in Punggur Lampung Tengah. A survey study was conducted by observing the mole cricket population and their damage since the rice was planted until the time of harvest. The resulThe results showed that the population of mole cricket is highly found in 1-5 weeks after planting. In the weeks that followed until rice harvested, the mole crikcet population decreased not be found before the harvest. Like the mole crikcet populations, the rice damage is due to an mole cricket attack only found until the 5th and 6th week after planting, and no damage after the 11th week.